Strategi Pengelolaan Lanskap Wisata di Perkampungan Budaya Betawi Setu Babakan Jakarta - Effendi, Melana; Nurhayati; Arifin, Hadi Susilo (Jurnal Lanskap Indonesia, 2024)
Setu Babakan Betawi Cultural Village (PBBSB) is a built landscape to save and maintain Betawi cultural traditions, including religion, culture, and Betawi arts with a community. It is fostered by the culture which includes all the results of ideas and works, both physical and non-physical, such as art, customs, folklore, literature, culinary, clothing, and architecture that are characterized by Betawi. PBBSB is an area designated by the government as a sustainable Betawi cultural preservation area with diverse tourism potential. This research aimed to map the existing conditions, inventory the potential tourist attractions, to calculate the carrying capacity, and to develop a management strategy for the PBBSB area. The research method used descriptive quantitative and qualitative analysis, carrying capacity assessment, and SWOT analysis. Based on the results of the study, the existing condition of the PBBSB area still remained to facilitate the activities that take place in this area, obtained several types of tourism that can attract the attention of visitors to the PBBSB area to realize and learn more about Betawi culture, the value obtained the carrying capacity of PCC > RCC > ECC = 22,923 > 4,031 > 3,084. This value indicates that the current carrying capacity of the PBBSB allows the area to move towards the sustainability of the Betawi cultural preservation area. More over several regional management strategies can be used to preserve the area of Setu Babakan Betawi Cultural Village.